How do I translate a sentence like this into predicate logic?
Always if an amateur chef bakes a burnt cookie, then nobody eats that burnt cookie.
My attempt is something like this ∀[chef’(x)∧ amateur'(x) ∧ burnt'(y) ∧ cookie'(y) ∧ bakes'(x, y)]→¬∃(z)[person'(z) ∧ eat'(z, y)]]
I am wondering how to do the adjectives and quantify over case with always while still using "nobody." Help appreciated:)
EDIT: This is considering Lewis' theory of adverbs of quantification, which uses unselective quantifiers to quantify over case. Here is the article: users.ox.ac.uk/~sfop0776/LewisQA.pdf I am sorry I didn't initially post it!